Corporate Social Responsibility and Collective OCB: A Social Identification Perspective - Wang, Xiao-Hua (Frank); Yang, Jun; Cao, Rujiao; Lee, Byron Y. (Frontiers in Psychology, 2019)
Although plenty of evidence has shown a positive relationship between collective organizational citizenship behavior (OCB) and unit or organizational performance, the antecedents of collective OCB are still understudied. In this study, we identify corporate social responsibility (CSR) as a new antecedent of firm-level collective OCB. Furthermore, we develop a collective social identification approach to examining the mechanism through which CSR may enhance collective OCB. Specifically, we propose and test a sequential mediation model in which CSR promotes organizational reputation. Organizational reputation, in turn, increases employees’ collective organizational identification and, consequently, enhances their collective OCB at the firm level. To test this model, we collected data from three different sources (i.e., HR director, CEO, and employees) from 160 firms in China. The results supported the hypotheses.